2017
DOI: 10.1016/j.medengphy.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Loading of the medial meniscus in the ACL deficient knee: A multibody computational study

Abstract: The menisci of the knee reduce tibiofemoral contact pressures and aid in knee lubrication and nourishment. Meniscal injury occurs in half of knees sustaining anterior cruciate ligament injury and the vast majority of tears in the medial meniscus transpire in the posterior horn region. In this study, computational multibody models of the knee were derived from medical images and passive leg motion for two female subjects. The models were validated against experimental measures available in the literature and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…The collision was limited to the cartilages and the menisci. The collision volume with the medial meniscus was estimated to be between 0.02 cm 3 and 0.78 cm 3 whereas that with the lateral meniscus ranged from below 0.01 cm 3 to 0.36 cm 3 .…”
Section: Movementsmentioning
confidence: 95%
See 1 more Smart Citation
“…The collision was limited to the cartilages and the menisci. The collision volume with the medial meniscus was estimated to be between 0.02 cm 3 and 0.78 cm 3 whereas that with the lateral meniscus ranged from below 0.01 cm 3 to 0.36 cm 3 .…”
Section: Movementsmentioning
confidence: 95%
“…In particular, gait analysis, jumping, standing, and other movements have been simulated and analyzed by various groups in physiotherapy, sport and rehabilitation research. [1][2][3] In total knee replacement surgeries, it has been demonstrated that malalignment causes increased wear of the implant, decreases longevity of the construct, and alters kinematics of the knee. [4][5][6] Simulations provide us insight into the intricate working of the musculoskeletal system, and augments our knowledge from experimental measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, soft tissues are deformable. The elastic properties of soft tissues within the knee remain challenging [7][8][9]. This sub-section gives a brief description of the elasticity of the soft tissues that is related to the surgical simulation.…”
Section: Soft Tissuesmentioning
confidence: 99%
“…The fiber reinforcement was discussed in [30] and biphasic linearity was used in [31]. Besides, many research efforts have been made on the meniscus, such as mechanical response in indentation experiments [7], contact mechanics using a sensor [32], micromechanical properties of extracellular matrix [33], loading in ACL injured knee [8], and structure and function relationships of tissues [34].…”
Section: Soft Tissuesmentioning
confidence: 99%
See 1 more Smart Citation